ISOLATION OF ASTRAGALIN FROM IRAQI CHENOPODIUM ALBUM - Mehdi, Anwar; Al-ani, Widad M K; Raoof, Ayad (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Chenopodium album L is the species of the genus chenopodium. The Greek name Chenopodium means goosefoot. The plant is native to Asia and Europe. The analysis of the constituents of the Iraqi plant was performed using gas chromatography and high-performance liquid chromatography techniques. Methods: Thin-layer chromatography (TLC) and high-performance TLC chromatographic techniques were used for the detection and isolation of the active constituent found in the plant. Spectral analysis such as nuclear magnetic resonance (NMR) and UV was used to confirm the chemical structure of the compound isolated. Results: Astragalin was isolated and identified by comparison with standard kaempferol 3-O-Î²-glucoside (astragalin) which was detected as the major glycoside in the polar fraction of the plant. Further, identification of the compound was performed by 1H-NMR spectroscopy. Conclusion: Astragalin is the major flavonoid glycoside found in the plant. Â 